2023
DOI: 10.3390/ma16124344
|View full text |Cite
|
Sign up to set email alerts
|

Peumus boldus Used in the Synthesis of ZnO Semiconductor Nanoparticles and Their Evaluation in Organic Contaminants

Caree Abigail García Maro,
Horacio Edgardo Garrafa Gálvez,
Osvaldo de Jesús Nava Olivas
et al.

Abstract: The high demand for nanomaterials in the field of industry and science has forced researchers to develop new synthesis methods that are more efficient, economical, and environmentally friendly. At present, the application of green synthesis has taken a great advantage over conventional synthesis methods because it helps with the control of the characteristics and properties of the resulting nanomaterials. In this research, ZnO nanoparticles (NPs) were synthesized by biosynthesis using dried boldo (Peumus boldu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 76 publications
0
0
0
Order By: Relevance
“…[188] As an example of what it is mentioned above, using the same mixture (Methylene Blue, Rhodamine B and Methyl Orange) of dyes, results indicated that in [197] complete degradation of the dyes occurred after 20 min, against efficiencies of 99% (Methylene Blue), 80% (Rhodamine B) or 67% (Methyl Orange) in 3 hours declared in [198]. These last results hardly compared with data from [186], in which is demonstrated that Rhodamine B is completely eliminated after 30 min. Another mixture of dyes (Methylene Blue and Methyl Orange) show the same disparity in results, since 90 min are needed to remove 95% and 75% of the respective cationic and anionic dye [181], and 45 min (99% Methylene Blue) or 35 min ( 97% Methyl Orange) as concluded in [194].…”
Section: Remarks To the Use Of Nanomaterials In The Removal Of Anioni...mentioning
confidence: 88%
See 1 more Smart Citation
“…[188] As an example of what it is mentioned above, using the same mixture (Methylene Blue, Rhodamine B and Methyl Orange) of dyes, results indicated that in [197] complete degradation of the dyes occurred after 20 min, against efficiencies of 99% (Methylene Blue), 80% (Rhodamine B) or 67% (Methyl Orange) in 3 hours declared in [198]. These last results hardly compared with data from [186], in which is demonstrated that Rhodamine B is completely eliminated after 30 min. Another mixture of dyes (Methylene Blue and Methyl Orange) show the same disparity in results, since 90 min are needed to remove 95% and 75% of the respective cationic and anionic dye [181], and 45 min (99% Methylene Blue) or 35 min ( 97% Methyl Orange) as concluded in [194].…”
Section: Remarks To the Use Of Nanomaterials In The Removal Of Anioni...mentioning
confidence: 88%
“…ZnSQD(h VB + ) + dye → degradation by − products (1) In this investigation [186], ZnO nanoparticles (average size 15-30 nm) were synthesized by biosynthesis using dried Peumus boldus leaves. The photocatalytic activity of these nanomaterials indicated that it is possible the quantitative degradation of Methylene Blue in three hours, 92% in the case of Methyl Orange also in the same time, and 100% degradation of Rhodamine B in 30 minutes.…”
Section: 3(photo)-catalytic Degradation Of Anionic and Cationic Dyes ...mentioning
confidence: 99%